Normative and Legal Regulation and Procedure for Bringing Officials to Liability for the Violation of the Right to Public Information’s Access - V. S. Vitkova (Bulletin of Kharkiv National University of Internal Affairs)
The article focuses on the violation of the right to public information’s access as a constituent of the constitutional right of a person and citizen to information. It is substantiated on the basis of received empirical data that in practice there are cases, where officials of public authorities, who are the stewards of public information, provide inaccurate / incomplete information, in connection with which there is a need for an adequate response to the offense. Attention is drawn to the fact that the provision of inaccurate information by public information’s stewards is one of the most complex problematic aspects for a number of reasons, in particular because of the complexity of verifying the information provided to the requester; the absence of possibility of proving intentionality in the actions of public information’s stewards; the complexity of the prosecution of authorized officials.